Meningkatkan Kemampuan Guru Menyusun RPP Berdifferensiasi Melalui Teknik Umpan Balik Di SDN Darurejo III - Suparmono Suparmono (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study is to describe: (1) The use of Feedback Techniques in improving teachers' abilities in preparing Differentiated Learning Implementation Plans at SDN Darurejo III Jombang for the 2022-2023 academic year semester 1; (2) Improving the ability of teachers to prepare Differentiated Learning Implementation Plans using the Feedback Technique at SDN Darurejo III Jombang for the 2022-2023 academic year semester 1. The method in this school action research used three cycles. The research subjects were 10 teachers at SDN Darurejo III for the 2022-2023 academic year semester 1. The research started from August to October 2022. The data collection method used interviews and documentation. The conclusions from this study are: (1) The feedback technique used at SDN Darurejo III Jombang for the 2022-2023 semester 1 academic year, is carried out through interviews or coaching about the Differentiated Learning Implementation Plan which has been compiled in three cycles. In addition, short notes are given on the results of the teacher's work to show things that still need further improvement/improvement. The sentences in the feedback can be in the form of comments, instructions or questions; (2) The teacher's ability to prepare a Differentiated Learning Implementation Plan using the Feedback Technique at SDN Darurejo III Jombang for the 2022-2023 academic year semester 1, has increased significantly in each indicator up to cycle III, namely 94.8%.